Exploring a chemical input free advanced oxidation process based on nanobubble technology to treat organic micropollutants - Wang, Bangguo; Wang, Lijing; Cen, Wenxi; Lyu, Tao; Jarvis, Peter; Zhang, Yang; Zhang, Yuanxun; Han, Yinghui; Wang, Lei; Pan, Gang; Zhang, Kaili; Fan, Wei (Elsevier, 2024)
Advanced oxidation processes (AOPs) are increasingly applied in water and wastewater treatment, but their energy consumption and chemical use may hinder their further implementation in a changing world. This study investigated the feasibility and mechanisms involved in a chemical-free nanobubble-based AOP for treating organic micropollutants in both synthetic and real water matrices. The removal efficiency of the model micropollutant Rhodamine B (RhB) by oxygen nanobubble AOP (98%) was significantly higher than for air (73%) and nitrogen nanobubbles (69%). The treatment performance was not significantly affected by pH (3–10) and the presence of ions (Ca2+, Mg2+, HCO3−, and Cl−). Although a higher initial concentration of RhB (10 mg/L) led to a slower treatment process when compared to lower initial concentrations (0.1 and 1 mg/L), the final removal performance reached a similar level (∼98%) between 100 and 500 min. The coexistence of organic matter (humic acid, HA) resulted in a much lower reduction (70%) in the RhB removal rate. Both qualitative and quantitative analysis of reactive oxygen species (ROSs) using fluorescent probe, electron spin resonance, and quenching experiments demonstrated that the contributions of ROSs in RhB degradation followed the order: hydroxyl radical (•OH) > superoxide radical (•O2−) > singlet oxygen (1O2). The cascade degradation reactions for RhB were identified which involve N-de-ethylation, hydroxylation, chromophore cleavage, opening-ring and final mineralisation processes. Moreover, the treatment of real water samples spiked with RhB, including natural lake water and secondary effluent from a sewage works, still showed considerable removals of the dye (75.3%–90.8%), supporting its practical feasibility. Overall, the results benefit future research and application of chemical free nanobubble-based AOP for water and wastewater treatment.
Keywords: Micro/nanobubble technology; Green technology; Reactive oxygen species; Organic micropollutant; Water and wastewater treatment